Antihyperlipidemia and Antihyperglycemic Studies of Arcangelisiaflava(L.)Merr. Phenolic Compound: Incorporation of In Vivo and In Silico Study at Molecular Level - Wahyuning Setyani; Hanny Setyowati; Dwi Hadi Setya Palupi; Hanievia Rahayunnissa; Maywan Hariono (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Yellow root had been extensively studied its potential as herbal medicines in many pharmacologic activities due to its alkaloid content namely berberine. To date, there is no study of the yellow root as the source of flavonoid to have anti-hyperglycemia and anti-hyperlipidemia effect. This present study focuses on flavonoid fraction being investigated its in vivo potential to reduce blood glucose level (165mg/dL at 28mg/kg of a fraction, peroxidase inhibition and catalase activation. The extract was obtained from the fresh yellow root, using the re-maceration method. These extracts were calculated as yield (%), then followed by a preliminary phytochemical investigation. The evaluation of anti-hyperglycemic and anti-hyperlipidemia activity was done using the fraction form of yellow root. The isolation of phenolic compounds was carried out by radial chromatography (chromatotron). The isolated compound was then structurally and computationally characterized using NMR and molecular docking, respectively. The fraction reduced the activity of peroxidase  (6.33%) at 14 mg/kg and increase catalase activity (15.74%) at 28 mg/kg of body weight of fraction, respectively. An effort to isolate the flavonoid in the fraction reveals a rutin-like structure, a flavonoid glycoside. This result, therefore, guides the utilization of rutin and its aglycon as the model of lipid peroxidase inhibitor and catalase activator upon in silico molecular docking.Keywords: anti-hyperglycemia, anti-hyperlipidemia, molecular docking, a phenolic compound, yellow root